2022
DOI: 10.1021/acs.jmedchem.2c00796
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis Reveals That Absolute Binding Free-Energy Calculations Approach Chemical Accuracy

Abstract: Systematic and quantitative analysis of the reliability of formally exact methods that in silico calculate absolute protein–ligand binding free energies remains lacking. Here, we provide, for the first time, evidence-based information on the reliability of these methods by statistically studying 853 cases from 34 different research groups through meta-analysis. The results show that formally exact methods approach chemical accuracy (error = 1.58 kcal/mol), even if people are challenging difficult tasks such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 86 publications
1
13
0
Order By: Relevance
“…Moreover, the free energy is a combination of many terms, which also increases the risks of errors and thus decreases precision and accuracy. Yet, a current meta-analysis of 853 studies from 34 different research groups showed that free energy methods were close to chemical accuracy (error = 1.58 kcal/mol) . On the other hand, binding enthalpy–entropy calculations have generally not been given much consideration with MD simulations, and there are limited studies, especially for complex systems. ,,,, It has been shown that an accurate binding enthalpy calculation is possible with a simplistic model, host–guest systems. ,, Notable efforts have also been made for complex systems to obtain relative binding enthalpies. , All of these studies have demonstrated that binding enthalpy calculations are sensitive to the choice of force field and sufficient sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the free energy is a combination of many terms, which also increases the risks of errors and thus decreases precision and accuracy. Yet, a current meta-analysis of 853 studies from 34 different research groups showed that free energy methods were close to chemical accuracy (error = 1.58 kcal/mol) . On the other hand, binding enthalpy–entropy calculations have generally not been given much consideration with MD simulations, and there are limited studies, especially for complex systems. ,,,, It has been shown that an accurate binding enthalpy calculation is possible with a simplistic model, host–guest systems. ,, Notable efforts have also been made for complex systems to obtain relative binding enthalpies. , All of these studies have demonstrated that binding enthalpy calculations are sensitive to the choice of force field and sufficient sampling.…”
Section: Discussionmentioning
confidence: 99%
“…This poses a massive challenge for the prediction accuracy of the barrier height, as already a mis-estimate by a single unit of k B T (or RT , respectively, i.e., 2.5 kJ/mol or 0.6 kcal/mol at physiological temperatures) causes a deviation of a predicted rate from the true rate by a factor of ∼3. For comparison, the average error of current free energy methods is ∼1.6 k B T , i.e., a factor of ∼14 in the error of k . This is a significant deviation compared to the chemically available variation in k within a compound library, which at best covers 4 orders of magnitude (see, e.g., the range of Hsp90-binding compounds available in refs , , , and ) and about 2 orders of magnitude for compounds with the same chemical scaffold for the A 2 adenosine receptor .…”
Section: Current Challenges In Rate Calculationsmentioning
confidence: 99%
“…10−17 A recent statistical analysis suggests that in silico absolute binding free energy calculations in conjunction with recent force fields can approach chemical accuracy, and are, thus, formally ready for blind screening in drug discovery. 18 Despite the many success stories of the methods devised for the calculation of standard protein−ligand binding free energies, achieving accurate estimates of the binding affinity for two proteins remains very challenging, even in less complex cases. 19 One of the reasons is the conformational changes of the binding partners in the course of recognition and association being appreciably more complex than in the case of protein binding of a ligand.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Since the pioneering work of Hermans and Shankar, who, for the first time, introduced a restraining potential to alleviate the difficulty in capturing the large change in configurational entropy as two molecular objects associate, methods to determine the standard protein–ligand binding free energy leaning on the introduction of geometric restraints have been developed at an increasing pace and are now broadly adopted in the fields of physical, biological, and medicinal chemistry. A recent statistical analysis suggests that in silico absolute binding free energy calculations in conjunction with recent force fields can approach chemical accuracy, and are, thus, formally ready for blind screening in drug discovery …”
Section: Introductionmentioning
confidence: 99%